Ensuring Sufficient Trough Plasma Concentrations for Broad-Spectrum Beta-Lactam Antibiotics in Children With Malignancies: Beware of Augmented Renal Clearance! - André, Pascal; Diezi, Léonore; Dao, Kim; Crisinel, Pierre Alex; Rothuizen, Laura E.; Chtioui, Haithem; Decosterd, Laurent Arthur; Diezi, Manuel; Asner, Sandra; Buclin, Thierry (Frontiers in Pediatrics, 2022)
Introduction Broad-spectrum beta-lactams are commonly prescribed for empirical or selective treatment of bacterial infections in children with malignancies. In the immunocompromised, appropriate concentration exposure is crucial to ensure antimicrobial efficacy. Augmented renal clearance (ARC) is increasingly recognized in this population, and raises concern for unmet concentration targets. We conducted a retrospective evaluation of meropenem and piperacillin exposure in our hospital’s pediatric hematology-oncology patients. Materials and Methods We compared trough levels of meropenem and piperacillin in a cohort of unselected pediatric hematology-oncology patients stratified based on their estimated renal function as decreased, normal or with ARC and on their neutrophil count. Results Thirty-two children provided a total of 51 meropenem and 76 piperacillin samples. On standard intermittent intravenous regimen, 67% of all trough plasma concentrations were below targeted concentrations. In neutropenic children with bacterial infection, all meropenem and 60% of piperacillin levels were below target. Nearly two-thirds of total samples came from children with ARC. In these patients, antimicrobial exposure was insufficient in 85% of cases (compared to 36% in the decreased or normal renal function groups), despite a dosage sometimes exceeding the maximum recommended daily dose. Under continuous infusion of piperacillin, only 8% of plasma levels were insufficient. Discussion Intermittent administration of meropenem and piperacillin often fails to ensure sufficient concentration exposure in children treated for malignancies, even at maximal recommended daily dosage. This can in part be attributed to ARC. We recommend thorough assessment of renal function, resolute dosage adjustment, continuous infusion whenever possible and systematic therapeutic drug monitoring.